Resiliensi pada Guru PAUD Honorer - Windi Safitri; Latifah Nur Ahyani (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This research aims to better understand aspects of resilience in honorary PAUD teachers through aspects of social support, individual abilities and interpersonal skills. The method used in this research is qualitative with a phenomenological approach where this research was conducted in Dempet District, Demak. This research involved 3 research informants who were honorary PAUD teachers with data collection methods using observation and interviews and data analysis using coding. The results of the research showed that the three informants often expressed things about self-defense, trust, social support and how to hone the informants' internal and interpersonal skills so that they were able to survive in carrying out their duties as honorary teachers in different ways. This shows that the three informants have good resilience even though the three aspects have similarities in social support from family and co-workers, and the differences in aspects of individual abilities and aspects of interpersonal skills lie in the way the informants look for work outside, apply new learning to their students, and differences in getting negative and positive responses from student parents.